Software fires detection and extinction for forest - Utande González de la Higuera, Nuria; García Seco, Juan Carlos (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
This article shows the most usual fire detection and forest extinction application technologies at present. We will see all different methods used by these applications that can be found in the Market and some examples. Also, some basic questions about the most influent parameters when a fire must be extinct are shown. Finally, after having shown all the technologies, we will build a model about an intelligent system which not only detects, but also extinguish wildfires
Keywords: bayesian network; ontologies; wildfire detection; IJIMAI